Impact force profile and failure classification of reinforced concrete bridge columns against vehicle impact - Do, T.; Pham, Thong; Hao, Hong (Pergamon, 2019)
Numerical simulations are utilized in this study to define the impact force profile generated by vehicle collisions on reinforced concrete bridge columns (RCBCs) and classify the dynamic responses and failure of the columns under collision events. The results indicate that both the column properties (i.e. dimension of the cross-section and concrete strength) and initial conditions of vehicles (i.e. vehicle velocity, engine mass, and vehicle mass) play a crucial role in determining the impact force profile from the vehicle collision. A new vehicle impact force model is proposed for engineers to use in design of RCBCs under vehicle collisions in which the influence of shear failure of the column on impact force is considered. Based on the shear mechanism of RCBCs under impact events, the maximum dynamic shear capacity of a column is defined. Furthermore, the bending moment and shear force distributions, as well as the failure mode of RCBCs have been classified into two categories, i.e. flexural response and shear response governed failure with respect to the peak impact force (PIF) on the column. For the flexural response governed failure mode, flexural cracks at the intermediate sections are formed in the positive side of the column, while the diagonal shear or punching shear failure at the impact area together with negative flexural-shear cracks occur in the column if the shear failure mode dominant the column responses.